Tears of clouds / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2022)
The dark murky clouds started to cry Their heavy tears fell to the ground Thunder came and screamed in the sky Hard blows of wind made a scary sound. Trees and weeds were swaying and shaking rapidly As if they were experiencing the greatest fear All on the surface were drenched and chilly While the sky was generously pouring water